Electoral reform in Prince Edward Island: A case study in deliberative democracy - Greenan, Mark (University of Ottawa (Canada), 2008)
This thesis examines the political theory of deliberative democracy, as elucidated by Habermas, through a case study of the electoral reform process in Prince Edward Island. For deliberative democrats like Habermas, public debate ideally possesses an epistemic, or truth-tracking, dimension. After a through discussion of the reform process in that jurisdiction, complemented by interviews with important actors in that process, the public debate on electoral reform in PEI is evaluated in terms of its correspondence with the idealistic presuppositions of deliberative democracy. It is argued that, due to low levels of public knowledge and problematic media coverage of the issue, the PEI electoral reform process provides little empirical support for the theory of deliberative democracy. Examining the dynamics of this case of public deliberation allows us to identify the factors that impede reasoned public deliberation in contemporary society.
Keywords: Political Science, General.